Poly(2‐vinylpyridine)‐Based Polymers as an Efficient Affinity Material for the Detection of Airborne Phenol. Issue 7 (29th April 2015) - Linke, Alexander; Schmidt, Manfred; Waldvogel, Siegfried R.
Abstract Phenol is an omnipresent compound in various situations. Its acute toxicity makes alternative tracing methods desirable. Highly potent affinity materials based on polyvinyl pyridine allow an efficient tracing of this particular airborne compound. Their performance over, for example, benzene is tremendously superior. In combination with a simple cyclodextrin derivative an array allows differentiation among such aromatic competitors. Owing to the high affinity of these polymers for phenol, quartz microbalance‐based tracing is able to detect phenol below the parts per million range. This was previously not possible with other affinity materials.